2021
DOI: 10.1101/2021.02.27.21252585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with antenatal care service utilization among women with children under five years in Sunyani Municipality, Ghana

Abstract: Background: Maternal and neonatal mortality remains a public health burden around the globe most especially in developing countries. A well utilized antenatal care (ANC) is however among the identified interventions to reduce this burden of maternal and neonatal mortality rates. A lot of factors therefore predispose, enable and cause mothers to identify the need to utilize this service (ANC). Aims/objectives: The aim of this study was to determine factors associated with the utilization of ANC service among po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
(65 reference statements)
3
11
2
1
Order By: Relevance
“…40 The prevalence of ANC4 + reported in this study is relatively lower than the 95.6%, 52.44%, 58.53% and 90.4% ANC4 + reported in other SSA countries. [41][42][43][44] Again, the prevalence of PNC observed in this study is comparatively lower than that in studies in Ghana (74%), 45 Ethiopia (51.2%) 46 and the pooled prevalence in SSA (52.48%). 47 The prevalence of SBA is higher than that of a previous study reporting 39.9% of SBA in Mali.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…40 The prevalence of ANC4 + reported in this study is relatively lower than the 95.6%, 52.44%, 58.53% and 90.4% ANC4 + reported in other SSA countries. [41][42][43][44] Again, the prevalence of PNC observed in this study is comparatively lower than that in studies in Ghana (74%), 45 Ethiopia (51.2%) 46 and the pooled prevalence in SSA (52.48%). 47 The prevalence of SBA is higher than that of a previous study reporting 39.9% of SBA in Mali.…”
Section: Discussioncontrasting
confidence: 81%
“…The overall prevalence of maternal healthcare utilisation was 45.6% for ANC4+, 74.7% for SBA and 25.5% for PNC which are higher than (30% ANC4 + and 38% SBA) those reported in the 2001 DHS 40. The prevalence of ANC4 + reported in this study is relatively lower than the 95.6%, 52.44%, 58.53% and 90.4% ANC4 + reported in other SSA countries 41–44. Again, the prevalence of PNC observed in this study is comparatively lower than that in studies in Ghana (74%),45 Ethiopia (51.2%)46 and the pooled prevalence in SSA (52.48%) 47.…”
Section: Discussioncontrasting
confidence: 79%
“…Staying in a secured partnership is suggested to provide adherence to the services, financial support, and accompaniment to ANC clinics which enhances a positive service utilization either by married women or for those women who were in a partnership for some time as compared to women who were never in a relationship 48,49 . This finding is also supported by other studies 50–52 . To address those pregnant women out of the union by reducing the associated stigma, and discrimination; societal advocacy to raise awareness shall be an important issue of concern.…”
Section: Discussionmentioning
confidence: 81%
“…According to the previous studies, women’s education, education level of the woman, husband’s education education level of her husband, place of residence, planned pregnancy, family income and household wealth index have been reported as determinants of antenatal care use [ 5 , 19 ]. Several other studies have also shown that living in rural areas, low education level, low economic welfare quintile, low income, and being single predispose women to avoid using antenatal care services [ 20 – 22 ].…”
Section: Methodsmentioning
confidence: 99%